Dampak Transformasi Digital Pada Pasar Tradisional - Wulandari, Dyah Sri; Tomanggor, Agustina Hotma Uli (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
This study aims to determine the impact of digital transformation on traditional markets, using descriptive qualitative methods with secondary and primary data sources with research locations in South Kalimantan. The result is that Digital Transformation has two impacts, namely positive impacts and negative impacts and there is still a lack of ability to transform digitally in some MSMEs in traditional markets, for the positive impact on MSMEs that have implemented digital marketing is that it makes it easier for consumers to transact both directly and online, marketing distribution becomes wider, and is able to increase turnover, While the negative impact on MSMEs that are not or have not been able to transform digitally is a decrease in sales turnover which has resulted in some MSMEs closing shops in traditional markets, from the data obtained in traditional markets in the South Kalimantan region in the last 5 years that the number of traders or MSMEs in traditional markets has relatively decreased from year to year, consumer visits to traditional markets have also decreased along with the development of technology changing the way consumers interact from face-to-face to traditional markets to digital marketing. With this research, it is hoped that MSMEs that have not yet digitally transformed can start doing digital marketing and for MSMEs that have done digital marketing to be able to improve their abilities to the maximum for the development of their business in the future.